Development Of Device Module And Material Based Processing Entrepreneurship For Madrasah Aliyah Students, The Zainul Hasan Genggong Model - Ainur Rofiq Sofa; Aznina Amadia Qurrotul Aini; Laila Geby Fitria; Inayatul Lussiyana; Nastangin; Agus Supriyanto; Shobirin; Baharudin Zaini (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
The first objective of this study was to develop a product which was a proper product-oriented module to support the craft and entrepreneurship learning for the processing materials for vocational school students. Second, this was aimed to describe the effectiveness of the product-oriented craft and entrepreneurship module for the processing materials for vocational school students. This research was research and development. The findings show that the validation result according to the material expert, media expert, learning practitioners and students indicates that the product-oriented module is proper to be implemented as a craft and entrepreneurship learning media for the processing materials. Next, the result of hypothesis testing obtained Sig. 0.000 which means that in the level of Sig. 0.05 there is an increase of the post test score compared to the pre test one. Therefore, it could be said that the product-oriented module was effective to be used in the craft and entrepreneurship learning for the processing materials in order to improve the understanding ability of vocational school students.